Answer:
![y-2=-5(x - 2)](https://tex.z-dn.net/?f=y-2%3D-5%28x%20-%202%29)
Step-by-step explanation:
Given:
The equations given are:
![y-2=-5(x - 2)\\X+ 7 = -4(X + 8)\\y - 3 = y(x + 4)\\y + 9 = x(x - 1)](https://tex.z-dn.net/?f=y-2%3D-5%28x%20-%202%29%5C%5CX%2B%207%20%3D%20-4%28X%20%2B%208%29%5C%5Cy%20-%203%20%3D%20y%28x%20%2B%204%29%5C%5Cy%20%2B%209%20%3D%20x%28x%20-%201%29)
Now, a linear function is of the form:
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
Where, 'm' and 'b' are real numbers and ![m\ne0](https://tex.z-dn.net/?f=m%5Cne0)
Equation 1: ![y-2=-5(x - 2)](https://tex.z-dn.net/?f=y-2%3D-5%28x%20-%202%29)
Simplifying using distributive property, we get:
![y-2=-5x+10\\y=-5x+10+2\\y=-5x+12](https://tex.z-dn.net/?f=y-2%3D-5x%2B10%5C%5Cy%3D-5x%2B10%2B2%5C%5Cy%3D-5x%2B12)
The above equation is of the form
. So, it represents a linear function.
Equation 2: ![X+ 7 = -4(X + 8)](https://tex.z-dn.net/?f=X%2B%207%20%3D%20-4%28X%20%2B%208%29)
Here, both sides of the equation has same variable 'X'. So, it will form an equation of 1 variable. So, it's not a linear function.
Equation 3: ![y - 3 = y(x + 4)](https://tex.z-dn.net/?f=y%20-%203%20%3D%20y%28x%20%2B%204%29)
Simplifying the above equation. This gives,
![y-3=yx+4y\\y-4y-yx=3\\y(1-4-x)=3\\y(-3-x)=3\\y=\frac{3}{(-3-x)}](https://tex.z-dn.net/?f=y-3%3Dyx%2B4y%5C%5Cy-4y-yx%3D3%5C%5Cy%281-4-x%29%3D3%5C%5Cy%28-3-x%29%3D3%5C%5Cy%3D%5Cfrac%7B3%7D%7B%28-3-x%29%7D)
This is not of the form of the linear function. So, it is also not a linear function.
Equation 4: ![y + 9 = x(x - 1)](https://tex.z-dn.net/?f=y%20%2B%209%20%3D%20x%28x%20-%201%29)
Simplifying the above equation. This gives,
![y+9=x^2-x\\y=x^2-x-9](https://tex.z-dn.net/?f=y%2B9%3Dx%5E2-x%5C%5Cy%3Dx%5E2-x-9)
This is not of the form of the linear function. So, it is also not a linear function.